Antidiabetic activity of bioactive fractions from Lepisanthes fruticosa (Roxb.) Leenh. fruits in streptozotocin-induced diabetic rats - Ahmad Hasan Salahuddin, Mirfat (2021)
Lepisanthes fruticosa (Roxb.) Leenh. or locally known as ceri Terengganu is an underutilised fruit species from the family Sapindaceae. The species was previously identified as a potent antioxidant source, but scientific information of the fruit species is still lacking and limited to in vitro. Therefore, the present study focused on both in vitro and in vivo evaluations of antioxidant and antidiabetic activities of L. fruticosa fruit extracts along with phytochemical profiling using liquid chromatography mass spectrometry (LC-MS/MS) approach. The different parts of the unripe fruits were successively extracted with hexane, chloroform, ethyl acetate and ethanol. Ethanolic seed crude extract was the most potent due to the strongest radical scavenging (IC50 0.178 ± 0.001 mg/mL), β-carotene bleaching (71%), α-glucosidase inhibition (IC50 1.873 ± 0.421 μg/mL) and highest total phenolic content (363.515 ± 46.296 mg GAE/g) (P<0.05). Bioassay-guided fractionation of the ethanolic seed crude extract showed fraction M4 as the most active due to the remarkable radical scavenging (IC50 0.128 ± 0.004 mg/mL), β-carotene bleaching (87%), α-glucosidase inhibition (IC50 0.341 ± 0.094 μg/mL) and greatest amount of total phenolic (1045.6 mg GAE/g) (P<0.05). Further LC-MS/MS analysis of the ethanolic seed crude extract and fraction M4 showed the presence of putative phytochemicals from various classes. Among the dominant compounds with notable antioxidant and antidiabetic properties were soyacerebroside II, α-kojibiose, genistein-7,4'-di-O-β-D-glucoside, daturametelin J and actinidioionoside which were detected in negative mode interface. The MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay revealed that L. fruticosa ethanolic extracts showed no cytotoxic effect against 3T3 (mouse embryonic fibroblast) cells up to concentration of 500 μg/mL. To investigate the in vivo antidiabetic effect of L. fruticosa ethanolic seed extract (LFSE) in Sprague Dawley rats, a combination of high fat diet (HFD) and low dose streptozotocin (STZ) (35 mg/kg body weight) was used. After 8 weeks of obesity induction, the STZ-induced diabetic rats were orally treated with 300 and 600 mg/kg body weight LFSE for 4 weeks. At the end of the experiment, significant (P<0.05) differences in body weight, water and energy intake between normal and diabetic groups were observed. There were no significant variations in the relative organ weights of heart, liver, lung and spleen of all diabetic groups as compared to normal control group. The LFSE treatment (600 mg/kg body weight) showed a more pronounced effect in anti-hyperglycaemic activities in both long-term (4 weeks) and short-term (2 hours) studies as assessed by oral glucose tolerance test (OGTT). The reduction of blood glucose level was comparable to metformin-treated group. The glucose lowering ability of LFSE (600 mg/kg body weight) was supported by its improved serum insulin level (32%) as compared to diabetic control. The treatment group also resulted in a significant (P<0.05) increase in plasma superoxide dismutase (SOD) (23%) and catalase (CAT) (75%) activities. Treatment with LFSE (600 mg/kg body weight) led to a significant (P<0.05) increase in the high density lipoprotein-cholesterol (HDL-c) (25%) when compared to diabetic control. The HDL-c level was also higher than all other groups at the end of study. Besides, LFSE (600 mg/kg body weight)-treated group exhibited a lower levels of aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP) than diabetic control group. No significant changes were seen in other liver and kidney functions. The findings may suggest that LFSE has potentials in reducing hyperglycaemia and oxidative stress-related biomarkers in HFD/STZ-induced diabetic rats. Although the underlying mechanisms remain elusive, the presence of various compounds could possibly be the key to the synergistic effects. Therefore, it can be concluded that L. fruticosa may be considered as a new potential therapeutic agent for diabetes management and its related complications.